The Contraries’ Progression: Romantic irony in the introductory poems of William Blake’s Songs of Innocence and of Experience - Weber Wanderlinde, William (2021)
In the vast bibliography on William Blake, scholars usually comment on the irony in his poetic works, but seldom they explain such comments. This paper is an attempt to understand the ironies present in some poems of Songs of Innocence and of Experience, while at the same time taking into consideration the dialectical quality of Blake’s thought. To do so, the concept of Romantic irony, developed by Friedrich Schlegel, is used, as it is also dialectical in its nature. In order to illustrate how Romantic irony is used to read the volume, an analysis of the introductory poems of each section, along with “Earth’s Answer” (the second introduction’s coda) and two plates which illustrate these poems, is made. The readings show some affinities between Blake’s and Schlegel’s way of thinking.